Implementation of Education Digitalization Policy in Central Kalimantan: IFP/Smart Board Utilization Readiness in Pulang Pisau Senior High Schools - Toto Pujiharyanto (Indonesian Scientific Publication, 2026)
This article maps implementation readiness for the education digitalization policy in Central Kalimantan Province through the use of Interactive Flat Panels (IFPs)/smart boards at senior high schools in Pulang Pisau Regency. Using an integrated lens (Edwards III + TAM + TPACK), the study distinguishes between “devices being available” and “devices being used meaningfully” by examining governance arrangements, infrastructure conditions, and pedagogical integration. A multi-site case study across nine schools (eight subdistricts) combined a review of policies/documents, administrative facility profiles (Kemendikdasmen Education Data), and a descriptive survey of school-level implementers (n = 25). The analysis shows that the use of IFPs/smart boards has the potential to strengthen interactive learning and support the Merdeka Curriculum. A consistent pattern was frequent and positively perceived use: 73.3% of respondents reported using IFPs at least five times per week, most commonly for collaborative projects (40.0%) and presentations (33.3%), while 80.0% reported using interactive features in more than 50% of sessions. Nevertheless, readiness varies according to operational conditions and governance, particularly reliance on personal hotspots when connectivity is limited (53.3%), uneven consistency in SOP implementation (20.0% reported written SOPs that were not implemented consistently; 13.3% reported relying only on informal SOPs), and technical-support arrangements (only 40.0% reported formal reporting channels with rapid responses and/or service-time targets). This study does not measure classroom learning outcomes; rather, it reports readiness and governance conditions that shape routine use. A feasible minimum implementation package should prioritize: (1) standardized SOPs for use, access, and asset governance; (2) sustained TPACK-oriented mentoring; and (3) tiered maintenance/helpdesk arrangements and utilization monitoring focused on usage indicators rather than procurement.